2023
DOI: 10.18332/tid/156842
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and determinants of smoking cessation in the Saudi Arabian Region of Jazan: A cross-sectional study

Abstract: INTRODUCTION Smoking cessation has significant health benefits. The purpose of this study is to assess the efficacy and related factors of smoking cessation therapies in the Jazan Region of Saudi Arabia. METHODS This is a cross-sectional study that took place at smoking cessation clinics in primary healthcare centers between January 2019 and January 2020. RESULTS This study enrolled a total of 103 people. The success rate for quitting smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…However, our study also highlights that occupational prestige, a distinct indicator of social status associated with one’s occupation( Ganzeboom and Treiman, 1996 ), posed a risk factor for relapse. This is aligned with a cross-sectional study in the Jazan Region of Saudi Arabia, finding that governmental employees demonstrated a lower percentage of smoking abstinence success than private-sector employees( Albasheer et al, 2023 ). In contrast, a study conducted in a Spanish hospital showed that participants who were managerial and senior technical staff and freelance professionals had significant hazard ratios of relapse after long-term follow-up compared to manual workers( Fernández et al, 2006 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, our study also highlights that occupational prestige, a distinct indicator of social status associated with one’s occupation( Ganzeboom and Treiman, 1996 ), posed a risk factor for relapse. This is aligned with a cross-sectional study in the Jazan Region of Saudi Arabia, finding that governmental employees demonstrated a lower percentage of smoking abstinence success than private-sector employees( Albasheer et al, 2023 ). In contrast, a study conducted in a Spanish hospital showed that participants who were managerial and senior technical staff and freelance professionals had significant hazard ratios of relapse after long-term follow-up compared to manual workers( Fernández et al, 2006 ).…”
Section: Discussionsupporting
confidence: 80%
“…Socioeconomic status inequalities in smoking relapse among populations in HICs have been extensively documented, focusing on social class and education level( Pisinger et al, 2011 , Albasheer et al, 2023 ). Few studies in low-income (LICs) and low- and middle-income countries (LMICs) have investigated the role of Socioeconomic status on smoking behavior.…”
Section: Discussionmentioning
confidence: 99%